Realizing Maqasid Al-Shari’ah in Shari’ah governance: a case study of Islamic banking institutions Malaysia - Muhammad Shahrul Ifwat, Ishak; Azmir Azri, Ahmad (2020)
This study explores how far the element of maqasid al-Shari’ah is realized through the practice of Shari’ah governance in Malaysia. Among the main bodies in Islamic banking institutions, Shari’ah governance plays a vital role in ensuring that all financial activities comply with Shari’ah rulings and its objective. Based on library research, this study analyzes secondary sources including books, articles and related documents to obtain a clear picture of the element of maqasid al- shari’ah in Shari’ah governance. The findings reveal that two special maqasid have been realized through the practice of Shari’ah governance in Malaysia: ensuring the viability of Islamic banking institutions and promoting transparency. While this study is limited due to the lack of empirical analysis, it could be considered as being among the preliminary studies on the topic of maqasid al-Shari’ah in Shari’ah governance.